2022
DOI: 10.1007/s41918-022-00169-z
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Strategies for Stabilizing Single-Atom Catalysts for Energy Storage and Conversion

Abstract: Well-defined atomically dispersed metal catalysts (or single-atom catalysts) have been widely studied to fundamentally understand their catalytic mechanisms, improve the catalytic efficiency, increase the abundance of active components, enhance the catalyst utilization, and develop cost-effective catalysts to effectively reduce the usage of noble metals. Such single-atom catalysts have relatively higher selectivity and catalytic activity with maximum atom utilization due to their unique characteristics of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 299 publications
0
41
0
Order By: Relevance
“…[ 6 , 7 , 8 , 9 ] As widely used OER catalysts, various transition‐metal based catalysts have been reported by many researchers. [ 10 , 11 , 12 , 13 ] Among various OER catalysts, 3d‐transition metal single atoms coordinated with planar four nitrogen atoms (M 1 N 4 ) have attracted ever‐increasing attention, due to the high atomic utilization and controllable coordination structure. [ 14 , 15 , 16 , 17 , 18 ] In particular, Co 1 N 4 was highly appealing because of the moderate binding strength for OER intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 , 7 , 8 , 9 ] As widely used OER catalysts, various transition‐metal based catalysts have been reported by many researchers. [ 10 , 11 , 12 , 13 ] Among various OER catalysts, 3d‐transition metal single atoms coordinated with planar four nitrogen atoms (M 1 N 4 ) have attracted ever‐increasing attention, due to the high atomic utilization and controllable coordination structure. [ 14 , 15 , 16 , 17 , 18 ] In particular, Co 1 N 4 was highly appealing because of the moderate binding strength for OER intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate the tendency of forming metal clusters, the Pt loadings were kept low (around 0.17 wt%). This, in fact, is the major limitation of this method, some practical applications physically need higher metal loadings [118]. The obtained slurry was dried and calcined at 333 • C and 473 • C respectively for 5 h each.…”
Section: The Co-precipitation Methodsmentioning
confidence: 99%
“…A single atom catalyst comprises highly dispersed single atoms of a metallic species onto a support material. However, innovative synthesis methods are needed given the thermodynamically instable nature of single atoms, so that the agglomeration phenomena during the synthesis and reaction processes (as surface free energy is lower in metal cluster form as compared to single atoms form [117]) can be avoided, if not, be reduced [118]. The description of these methods is presented in the following sub-sections, where some of the respective key remarks are summarized in Table 1.…”
Section: Synthetic Routes Towards Single Atom Catalystsmentioning
confidence: 99%
“…To this end, the single-atom catalyst with catalytically active sites atomically dispersed on supports is regarded as one of the most promising candidates as it can maximize atom utilization and create uniform active sites . However, many studies have shown that the single-atom catalyst does not necessarily achieve high catalytic performance. A major reason is the relatively low loading amount of single-atom active sites . Even though a single-atom catalyst with a high loading density can be synthesized, it may not remain stable under catalytic conditions. As such, the loading of single atoms onto supports has become an important topic in this research field and should be well addressed.…”
Section: Introductionmentioning
confidence: 99%
“…4−7 A major reason is the relatively low loading amount of single-atom active sites. 8 Even though a single-atom catalyst with a high loading density can be synthesized, it may not remain stable under catalytic conditions. 8−10 As such, the loading of single atoms onto supports has become an important topic in this research field and should be well addressed.…”
Section: Introductionmentioning
confidence: 99%